The Development of a Practice Set of Playing Pong Lang for Ceremonial Staff, The 10th Royal Funeral Administration Group, Khon Kaen Province: การพัฒนาแบบฝึกปฏิบัติการบรรเลงโปงลาง สำหรับเจ้าหน้าที่ปฏิบัติงานพิธี กลุ่มอำนวยการพิธีการศพที่ได้รับพระราชทานที่ 10 จังหวัดขอนแก่น - Unphim, Jirakit; Jaksen, Hirun; Kaenampornpan, Pornpan (Journal of Graduate MCU KhonKaen Campus, 2022)
The mixed methods research was conducted in this study to collect both quantitative and qualitative data. The objectives were to study the condition of the need for Pong Lang practice set for ceremonial staff, the 10th Royal Funeral Administration Group, Khon Kaen Province and to develop a Pong Lang practice set for ceremonial staff, the 10th Royal Funeral Administration Group, Khon Kaen Province by dividing into 2 steps: 1) The step before conducting the experiment to select a sample group of Pong Lang learners who were interested in practicing Pong Lang instruments from a survey created by the researcher; and 2) The step for conducting an experiment in the Pong Lang practice exercise. The sample group consisted of 15 ceremonial staff of the 10th Royal Funeral Administration Group, who were specifically selected. The tools used in the research included: 1) Opinion survey questionnaire on the need for practice of playing pong lang instruments 2) Pong Lang instrument practice exercise 3) the performance test of the Pong Lang instrument practice; and 4) Satisfaction questionnaire. The results of the research showed that the practice set developed for 10 weeks consisted of the following key contents: 1) Basic study of the Pong Lang instrument 2) Reading Thai notes 3) Learning about holding the Pong Lang wood and getting familiar with the Pong Lang instrument. 4) Practice memorizing the notes in Pong Lang pattern, 5) Practice reading the notes and clapping hands to the rhythm of the Nok Sai Bin Kam Tung pattern, and 6) the practice of playing the Pong Lang musical instruments in the Pong Lang pattern and Nok Sai Bin Kam Tung pattern according to the exercises. The efficiency of the practice set was 80.9/89.5, which was higher than the set threshold of 80/80, and the subjects were satisfied with the Pong Lang practice set with a mean of 4.76, which was at the criteria level with the most satisfaction. Therefore, it can be concluded that using the Pong Lang instrument practice set From the testing of the samples, the samples were effective in learning. The skill of playing the Pong Lang instrument was the highest. and satisfied with the Pong Lang instrument practice set.